2016
DOI: 10.1002/ejhf.467
|View full text |Cite
|
Sign up to set email alerts
|

The influence of iron deficiency on the functioning of skeletal muscles: experimental evidence and clinical implications

Abstract: Skeletal and respiratory myopathy not only constitutes an important pathophysiological feature of heart failure and chronic obstructive pulmonary disease, but also contributes to debilitating symptomatology and predicts worse outcomes in these patients. Accumulated evidence from laboratory experiments, animal models, and interventional studies in sports medicine suggests that undisturbed systemic iron homeostasis significantly contributes to the effective functioning of skeletal muscles. In this review, we dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 121 publications
(247 reference statements)
4
96
3
1
Order By: Relevance
“…As previously reported, iron participates in skeletal muscle function [69]. Although this issue has been poorly addressed in age-associated muscle changes, research on diseases such as heart failure and chronic obstructive pulmonary disease have suggested that iron deficiency may impair physical capacity.…”
Section: Nutritionmentioning
confidence: 95%
See 2 more Smart Citations
“…As previously reported, iron participates in skeletal muscle function [69]. Although this issue has been poorly addressed in age-associated muscle changes, research on diseases such as heart failure and chronic obstructive pulmonary disease have suggested that iron deficiency may impair physical capacity.…”
Section: Nutritionmentioning
confidence: 95%
“…Iron deficiency has been linked to several alterations such as decreased physical capacity and muscle mass; altered oxidative-to-glycolytic fiber ratio; reduced myoglobin pool; decreased mitochondria and mitochondrial cristae density; and reduced oxidative metabolism with increased glycolytic activity [69]. Despite this information suggesting iron deficiency plays a role in impairing physical capacity, iron status has been poorly addressed in age-associated muscle changes.…”
Section: Etiology and Intracellular Pathways Involved In Aging-associmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of reduced iron availability on cardiac and skeletal muscle cells may be to impair oxygen storage through reduced myoglobin and to directly reduce energy generation by mitochondria and, thereby, the efficiency of the heart and skeletal muscle to maintain contractile strength and endurance (Jankowska et al, 2010;Frise et al, 2016;Stugiewicz et al, 2016). The effects of iron deficiency on patients with cardiac disease therefore go far beyond any reduction in oxygen supply but may contribute to directly to worsening cardiac or skeletal muscle function (Von Haehling et al, 2015).…”
Section: Pathophysiology Of Iron Deficiency In the Failing Heartmentioning
confidence: 99%
“…Spearman's rank correlation coefficient (R) is reflecting the interrelationship between the mRNA expression of respective genes (FTH -ferritin heavy chain; FTL -ferritin light chain; FPN1 -ferroportin type 1; TfR1 -transferrin receptor type 1; MB -myoglobin; HAMP -hepcidin) within H9C2 or L6G8C5 in the whole spectrum of iron concentration been performed mainly in the cells involved in systemic iron homeostasis, such as hepatocytes, macrophages, enterocytes, or erythroid precursor cells [24][25][26]. However, it is worth mentioning that local iron homeostasis may differ from the systemic one [27]; therefore, we aimed to investigate the molecular machinery present in the cells of high energy demand, such as cardiomyocytes and skeletal myocytes. In our study we confirmed the presence of the molecular machinery involved in iron import, export, storage, and regulation in rat cardiomyocytes H9C2 and myocytes L6, which represent cells of high energy demand.…”
Section: Discussionmentioning
confidence: 99%